Analysis of Trends in the Higher Education and Science as the Basis for Strategizing the Scientific and Innovative Activities in Regional Universities - E. A. Pahomova (Управленческое консультирование)
Aim of the article is to identify global, national and local trends in the development of higher education and science, which should be taken into account when strategizing the scientific and innovative activities of a regional university (in the conditions of the Kemerovo region — Kuzbass).Materials and methods. The methodological and theoretical basis of the study is the theory of strategy and the strategy methodology developed by V. L. Kvint (Moscow State University named after M. V. Lomonosov), which made it possible to substantiate the analysis of opportunities and threats as the initial stage of strategizing the scientific and innovative activities of a regional university. The methods of OTSW-analysis, economic-statistical analysis, comparative analysis were used Analytical and forecast documents of authoritative Russian and international organizations dealing with the problems of science and higher education were used.results. 12 trends of various levels are identified that determine the opportunities and threats for the strategic development of scientific and innovative activities in the universities of the Kemerovo region — Kuzbass. At the global level, these include a decrease in demand for higher education and the need for scientific and innovative diversification; the growth of the global research and development market, especially in certain niches; growth in the share of research and development funding by commercial organizations; influence on the research topics of the international agenda, including the UN sustainable development goals. The main national trends are instability and limited funding for research and development, the growing interest of the state in fundamental research; maintaining a low level of integration of universities with business with the growth of the innovative activity of the latter; the growing stratification of the domestic higher education. In the Kemerovo region — Kuzbass, the most important trends are the structural transformation of the traditional university system with increased competition among universities; limited demand for research and development, not corresponding to the economic importance of the region; creation of institutional foundations for the development of scientific and innovative activities and the strategic goals of Kuzbass for scientific and technological development, which determine promising areas of research.Conclusions. Based on the analysis of strategically significant trends, the first stage of the OTSW analysis was implemented, the opportunities and threats that determine the strategic development of research activities of the universities of the Kemerovo region — Kuzbass were identified.